Análise diferencial da terceirização de atividades-fim em uma indústria de linha branca brasileira - Assis, Ângelo Rafael Vieira de (2007)
The outsourcing is a consolidated business practice, however the studies on its impacts are rare, especially the financial ones. This study objective is to evaluate the impacts on the financial dimension of outsourcing decisions in a white goods industry that trade in national and international market. To accomplish this objective is necessary to know intentions of outsourcing, determine financial results and analyze them. It is applied a quantitative and qualitative approach, by exploratory, descriptive research and field work to perform case study, including documentary research and interviews with production managers, engineering, quality and administrative-financier, by differential analysis. Had not evaluated the cost subjective variables, the study of right-handed, opportunity and quality costs allows to visualize the positive contribution of the outsourcing for the financial results of the organization, which is more important because it operates in segments of market with reduced profit margins. In this context, is important to point out the contributions of the outsourcing for the increment of production levels, which generate gains of scale. The study also shows opportunities of improvement in the management of quality and work capital costs management as well as controls of the outsourcing processes.